Surface characterization of absorbing polymer films deposited on transparent glasses - Gonçalves, Débora; Travain, Silmar A.; Giacometti, José A. [UNESP]; Irene, Eugene A. (De Gruyter, 2008)
PANI films were deposited on glass substrates by in-situ polymerization and characterized by UV-VIS spectroscopy and atomic force microscopy. A method is developed to accurately analyze ellipsometric data obtained for transparent glass substrates before and after modification with absorbing polymer films. Surface modification was made with an overlayer such as polyaniline (PANI), which exhibits different optical properties by varying its oxidation state. First, the issue of using transparent substrates for ellipsometry studies was examined and then, spectroscopic ellipsometry was used to characterize absorbing overlayers on transparent glasses. The same methodologies of data analysis can be also applied to other absorbing films on transparent substrates, and deposited by different techniques.